2021
DOI: 10.1002/mnfr.202100552
|View full text |Cite
|
Sign up to set email alerts
|

Administration Time Significantly Affects Plasma Bioavailability of Grape Seed Proanthocyanidins Extract in Healthy and Obese Fischer 344 Rats

Abstract: Scope: Phenolic compounds are bioactive molecules that are associated with several health benefits. Metabolization and absorption are the main determinants of their bioavailability and bioactivity. Thus, the study of the factors that modulate these processes, such as sex or diet is essential. Recently, it has been shown that biological rhythms may also play a key role. Hence, the aim of this study is to evaluate if the bioavailability of a grape proanthocyanidin extract (GSPE) is affected by the administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…The chemical and reagents used in the current study had been previously reported by our group. [ 30 ] Briefly, acetone, acetonitrile, phosphoric acid (Sigma–Aldrich, Madrid, Spain), glacial acetic acid (Panreac, Barcelona, Spain), and methanol (Scharlab S.L., Barcelona, Spain) were all of HPLC analytical grade. Ultrapure water was obtained from a MilliQ Advantage A10 system (Millipore, Madrid, Spain).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The chemical and reagents used in the current study had been previously reported by our group. [ 30 ] Briefly, acetone, acetonitrile, phosphoric acid (Sigma–Aldrich, Madrid, Spain), glacial acetic acid (Panreac, Barcelona, Spain), and methanol (Scharlab S.L., Barcelona, Spain) were all of HPLC analytical grade. Ultrapure water was obtained from a MilliQ Advantage A10 system (Millipore, Madrid, Spain).…”
Section: Methodsmentioning
confidence: 99%
“…A microsolid-phase extraction (μSPE) was carried out, as it was previously reported by our group, [30,37] in order to eliminate interferences and quantify the GSPE-derived metabolites. Briefly, the microcartridges were sequentially conditioned with 250 μL of methanol and 250 μL of 0.2% acetic acid.…”
Section: Micro-solid Phase Serum Phenolic Metabolites Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 98 ] While it is still unknown how these contrasting changes may translate to physiological outcomes, another recent study also noted that GSPE administered in rats at the start of the rest phase exhibited higher bioavailability as compared to the active phase. [ 99 ] Hironao et al. [ 100 ] also reported that cacao procyanidin extract administered only at the start of the rest phase exerted protective effects against postprandial hyperglycemia in mice.…”
Section: Dietary Components Intake Timing and Their Interaction With ...mentioning
confidence: 99%
“…In this regard, some studies have already shown that phenolic compounds from grape seed extract (GSPE), only when administered at night, enhanced the energy profile and improved mitochondrial function and oxidation in the liver in diet-obese male Fischer 344 rats [ 5 ]. Interestingly, in these animals, the bioavailability of the phenolic compounds of this extract was dependent on the moment of administration, increasing the amount of some microbial metabolites when administered at night [ 6 ]. Unfortunately, there are not many studies that focus on the evaluation of the impact on the consumption of bioactive compounds under different photoperiods.…”
mentioning
confidence: 99%